An Ancient >200 m Cumulative Normal Faulting Displacement Along the Futagawa Fault Dextrally Ruptured During the 2016 Kumamoto, Japan, Earthquake Identified by a Multiborehole Drilling Program. (24th January 2022) - Shibutani, Susumu; Lin, Weiren; Sado, Koichiro; Aizawa, Akihiro; Koike, Katsuaki
Abstract: The Mw 7.0 mainshock of the 2016 Kumamoto earthquake sequence was triggered by dextral rupture of the Futagawa fault within the Aso volcanic region, Southwestern Japan. To reproduce its faulting patterns and to reveal the geological and geophysical characteristics of the fault and surrounding lithological units, we report the results of a multiple‐borehole drilling program penetrating the Futagawa fault zone. By combining core descriptions with geophysical logs, we identified >200 m of normal faulting displacement along the currently dextral strike‐slip Futagawa fault. Considering previous kinematic and chronological studies of the fault, we interpret that the Futagawa fault dominantly slipped as a normal fault in a short period (∼300–87 ka) before switching to its current transtensional (dominant strike‐slip) regime ∼87 ka caused by a local change in the stress field associated with the termination of the Aso caldera‐forming eruptions. In the main borehole, three damage/slip zones were penetrated at depths of ∼354, 461, and 576 m. The 461 damage zone was identified as ∼45 m in vertical thickness and thicker than the other damage zones (∼3–6 m vertically) and was characterized by high fracture density and the presence of strike‐slip slickenlines. Depth profiles of physical properties revealed different patterns near the three damage zones; both the resistivity and the P‐wave velocity showed stronger deterioration at the 461 damage zone than the others. Based on these geological and geophysical observations, we suggest that the 461 damage zone is the primary candidate for seismogenic faulting during the 2016 Kumamoto earthquake mainshock. Plain Language Summary: The Mw 7.0 mainshock of the 2016 Kumamoto earthquake sequence was caused by slipping along the Futagawa fault within the Aso volcanic region of Southwestern Japan. To investigate its faulting patterns, the geological structure and geophysical properties of the fault and surrounding units, we report the results of the Futagawa fault drilling project in which multiple boreholes were drilled through the fault zone. We found >200 m of normal faulting displacement along the currently strike‐slip Futagawa fault. Taking previous studies together, we interpret that the Futagawa fault dominantly slipped as a normal fault in a short period (∼300–87 kyr ago) before switching to its current strike‐slip mode ∼87 kyr ago caused by termination of the Aso caldera‐forming eruption sequence. In the ∼700 m‐deep main borehole, three damage zones were identified. The second damage zone at ∼461 m depth was more strongly damaged than the others. In addition, the physical properties revealed different change patterns near the three damage zones and showed strongest deterioration at the 461‐m damage zone. Based on geological and geophysical observations, we suggest that this damage zone is the primary candidate that caused the 2016 Kumamoto earthquake mainshock. Key Points: Multiborehole drilling through the currently dextral Futagawa fault zone reveals >200 m of cumulative normal‐sense displacement The switch from normal to dextral motion was probably due to termination of the Aso caldera‐forming eruption sequence at ∼87 ka Geological and geophysical data suggest the fault zone at ∼461 m depth experienced dextral‐sense slip during the 2016 Kumamoto earthquake